The Impact of Changing Storage Area on Flood Magnitude and Occurrence - Kusumastuti, D.I. (Civil Engineering Dimension, 2012)
This study focuses on the impact of combined catchment and storage upon flood occurrences and flood peaks. A significant factor that plays an important role of the combined catchment and storage is the ratio of contributing catchment area to storage area (AC/AS) where the impact significantly shows increasing frequency of storage overflow and flood peaks with the increasing of AC/AS. Some case studies examined in this work, i.e. Way Pegadungan (Lampung, Sumatra) and NagaraRiver (South Kalimantan) catchments show similar behavior. Swamps located on the sides of downstream of Way Pegadungan as well as Nagara River act as storages during flood events. The dyke which was planned to be built increases the ratio of AC/AS significantly as storage area reduced considerably. This has an impact on flood peaks which can increase considerably. The improved understanding of these process controls will be useful in assisting the management of such catchments, particularly to assist in flood prevention and mitigation.